Ruptured Arteriovenous Malformation Presenting with Kernohan’s Notch - Christopher F. Dibble; Michael P. Wemhoff; Tarik Ibrahim; Deanna Sasaki-Adams; Sten Solander; Anand V. Germanwala (Case Reports in Neurological Medicine)
AVMs are congenital lesions that predispose patients to intracranial hemorrhage and resultant neurological deficits. These deficits are often focal and due to the presence of local neurologic disruption from hemorrhage in the contralateral cerebral hemisphere. We present a rare case of a patient with ipsilateral neurological deficits due to Kernohan’s Notch phenomenon resulting from hemorrhage from an AVM. A 31-year-old woman with seizures underwent MR and angiographic imaging which confirmed an unruptured left parietal AVM. The patient declined treatment and presented with obtundation 4 years later. Imaging revealed an acute left parietal ICH and SDH with significant mass effect. The patient underwent emergent hemicraniectomy and hematoma evacuation. Postoperatively, she made significant improvement and was following commands contralaterally with ipsilateral hemiplegia. MR imaging revealed right Kernohan’s Notch. The patient had significant rehabilitation with neurological improvement. She eventually underwent elective embolization followed by subsequent surgical resection and bone replacement. Three years from the initial hemorrhage, the patient had only mild left-sided weakness and ambulates without assistance. A false localizing sign, Kernohan’s Notch phenomenon, should be considered in the setting of AVM hemorrhage with paradoxical motor impairment and can be identified through MRI.